Direct-To-Implant and 2-Stage Breast Reconstruction After Nipple Sparing Mastectomy: Results of a Retrospective Comparison. Issue 4 (October 2019) - Pallara, Tiziano; Cagli, Barbara; Fortunato, Lucio; Altomare, Vittorio; Loreti, Andrea; Grasso, Antonella; Manna, Elena; Persichetti, Paolo
Abstract : Abstract: Breast reconstruction after nipple sparing mastectomy (NSM) plays, nowadays, a fundamental role in breast cancer management. There is no consensus on the best implant-based reconstruction technique, considering 2 stages (expander-prosthesis) or direct-to-implant (DTI). A retrospective review of consecutive adult female patients who underwent NSM with breast reconstruction over a 3-year period (January 2013 to December 2015) was performed. Patients were divided into 2 groups according to the type of reconstruction: expander/prosthesis (group A) and DTI (group B). Anamnestic data were collected. Number and type of procedures, complications and esthetic satisfaction were registered and compared. Fifty-six patients were included in group A (34.6%) and 106 in group B (65.4%). Complications associated with the 2 types of breast reconstruction were not different ( P = 0.2). Patients in group A received a higher number of total surgical procedures (considering revisions, lipostructures and contralateral symmetrizations) than those in group B (2.5 ± 0.69 and 1.88 ± 1.02, P = 0.0001). Satisfaction with breast reconstruction resulted higher in group A (7.5 ± 2.6 and 6 ± 1.9, P = 0.0004). At the multivariate analysis, chemotherapy and radiotherapy were not correlated with complications, regardless of the group (odds ratio, 0.91 and 2.74, respectively). Radiotherapy and chemotherapy did not even influence the esthetic result, regardless of the group ( P = 0.816 and P = 0.521, respectively). Prosthetic breast reconstructions, both in a single and in 2 stages, are welcomed by patients and have relatively low and almost equivalent complication rates, independent of other factors such as chemotherapy, radiotherapy, lymphadenectomy, smoking and age. In our experience, 2-stage breast reconstruction, although requiring more operations, is associated with a higher esthetic satisfaction. Patients who perform a DTI breast reconstruction after NSM should be informed of the high probability of surgical revision.